Allocative Efficiency : Better Align Social Protection Resources with National Policy - Sabbih, Mostafa Amir; Coudouel, Aline (World Bank, Washington, DC, 2021)
Policy making requires categorizations, which are commensurate with strategic directions. Social protection is a term, which can be used to describe a broad range of programs. The National Social Security Strategy (NSSS) of Bangladesh has a rather broad scope, covering what many define as safety nets or social assistance, as well as insurance against some risks, programs addressing shocks, and interventions focused on employment or productivity. This policy note analyses the extent to which resources are allocated efficiently, in line with national strategies and priorities. In particular, this policy note discusses the importance of policy relevant categorization/classification of programs; gaps and challenges in resource allocation in respect to the needs of different demographic and socio-economic groups and/or in respect to functions Social protection (SP) programs are supposed to play. It proposes reforms which could address some of the challenges identified.